Sinergi Syariat dan Hakikat pada Majelis Sholawat As-Sa’adah di Sidoarjo - Solihah, Maratus; Rafsanjani, Anugerah Zakya (Postgraduate Studies UIN Sunan Ampel Surabaya, 2025)
This study examines the synergy between fiqh and Sufism in shaping the harmony of sharia and spiritual values through the activities of the As-Sa’adah Sholawat Council in Sidoarjo, East Java. The study highlights how local Islamic traditions sustain both legal and mystical dimensions of religious life in contemporary Javanese Muslim communities. Using a qualitative method with a case study approach, data were collected through observation, interviews, and documentation involving council members and religious leaders. The analysis employed the Miles and Huberman model with triangulation to ensure validity. The findings reveal that the As-Sa’adah Council integrates fiqh and Sufism through communal prayers, tawasul, tahlil, and sholawat, balancing external discipline (sharia) with inner spirituality (haqiqat). This harmony reflects the Javanese concept of laku, where religious practice becomes a path toward ethical refinement and divine closeness.